SOSIALISASI PENINGKATAN WIRAUSAHA DENGAN MEMANFAATKAN TEKNOLOGI PADA GURU SMA DARUL ILMI MURNI JL. KARYA UJUNG – TITI KUNING SUMATERA UTARA - Debi Masri; Furqan; Yogi Putra (Cattleya Darmaya Fortuna, 2022)
Based on the results of community service carried out by Darul Ilmi Murni Private High School teachers, that teacher knowledge related to increasing entrepreneurship is very minimal, especially by using technology as a medium for increasing entrepreneurship, so that knowledge transfer is limited to Darul Ilmi Murni Private High School students.